The impact of terrorism on well-being: Evidence from the Boston Marathon Bombing - Andrew E Clark; Elena Stancanelli; Orla Doyle (University College Dublin, UCD School of Economics, 2017)
A growing literature concludes that terrorism impacts the economy, yet less is known about its impact on utility. This paper estimates the impact of the 2013 Boston Marathon Bombing on well-being, by exploiting representative U.S. daily data. Using both a regression discontinuity and an event study design, whereby the 2012 Boston marathon serves as a counterfactual, we find a sharp reduction in well-being, equivalent to a two percentage point rise in annual unemployment. The effect is stronger for women and those living in nearby States, but does not persist beyond one week, thus demonstrating the resilience of well-being to terrorism.
Keywords: I31; J21; J22; F52; 330; Well-being; Terrorism; Regression Discontinuity Design; Differences-in-Differences